Mainstreaming Adaptation in National Development Planning - Casado-Asensio, Juan (OECD Development Co-operation Working Papers, 2016)
This Working Paper explores progress in the integration or mainstreaming of adaptation and related objectives into national development planning. It first provides an overview of the international mechanisms, including finance, to support the mainstreaming of climate change adaptation into development planning and policies in developing countries. Through a review of relevant planning documents in fifteen developing countries, it then examines key features in adaptation planning and mainstreaming of adaptation into development planning. These countries were because they have been amongst the highest recipients of adaptation-related bilateral development finance. The research provides a snapshot of current practice. Despite heightened international efforts to support developing countries, evidence of mainstreaming adaptation was only found in a few of the countries and in a few of the sectors studied here. It also found that where mainstreaming is occurring, linkages exist with other policy objectives including poverty reduction, promoting biodiversity and ecosystems, and urban and rural development. The findings may be a useful starting point to guide policy-relevant research, such as to what extent mainstreaming may be occurring on the ground (or not) and how well this progress is reflected in planning documents, as well as how to improve the effectiveness of development co-operation targeting adaptation. The paper may also help inform international efforts under the UNFCCC that are designed to support developing countries to mainstream adaptation priorities into development planning and policy